Deriving a Fault Resilience Metric for Real-Time Systems - Nascimento, Flávia Maristela; Lima, George; Lima, Verônica Cadena (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2009)
Most real-time systems are required to comply with strict time and logical requirements even in the presence of faults. Although scheduling policies and schedulability analyses have been extended to deal with fault tolerance, not much attention has been given to measuring the fault resilience of such systems. Usually, worst-case error patterns are artificially assumed and system correctness is checked. However, such patterns do not represent the capacity of the system to tolerate faults, nor consider the overall system behavior in the presence of faults. In this paper we define a fault resilience metric and present a simulation-based analysis. Then we show how simulation results can be statistically analyzed.